ISOLASI DAN IDENTIFIKASI SENYAWA TOKSIK PADA SPONS DARI PERAIRAN GILI SULAT-LOMBOK - Dira Swantara, I M.; Supriyono, Agus; Trinoviani, Mila (Jurnal Kimia (Journal of Chemistry); Vol. 1, No. 2 Juli 2007)
The isolation and identification of toxic compound on sponge from BPPT collection sub P3-TFM derived from Gili Sulat, Lombok waters has been conducted. The extraction applied was maceration method, which was totally conducted using three kinds of solvents namely, methanol, dichloromethane, and n-hexane. The total extract obtained was then partitioned into liquid using ethyl acetate and n-butane respectively. The most toxic extraction was separated by chromatography column with sephadex LH-20 as the stationary phase and methanol as the mobile phase. Identification of the active isolate was conducted by gas chromatography - mass spectroscopy with the aim of Wiley 275.L. database. Toxin test to sponge of BPPT collection sub P3-TFM showed that SL2 sponge was proved to be the most toxic one. The most toxic fraction of SL2 sponge at LC50 at 100 ppm was assumed to be the combination of 7 compounds, namely benzene acetatic acid (8.9%), dioktil hexadioate (4.5%), bis (2etilheksil) 1.2-benzeneboksilat (53.1%), 2, 6, 10, 15, 19, 23 hexamethyl 2, 6, 10, 14, 18, 22-tetracosahexene, (17.1%), nonacosane (7.8%), cholesterol (3.8%) and eicosane (4.8%).
Keywords: isolation, identification, toxic compounds, sponge